Let [tex]m=x^{2}+3[/tex]

Which equation is equivalent to [tex](x^{2}+3)^{2} +7x^{2} +21=-10[/tex]

A.) [tex]m^{2}-7m+10=0[/tex]
B.) [tex]m^{2}-7m+31=0[/tex]
C.) [tex]m^{2}+7m+10=0[/tex]
D.) [tex]m^{2}+7m+31=0[/tex]

Answer :

Hi1315

Answer:

[tex]{m}^{2} +7m + 28 = 0[/tex]

Step-by-step explanation:

Given that,

[tex]m = {x}^{2} + 3[/tex]

We know that,

[tex] {x}^{2} = m- 3[/tex]

Now look at the sum

[tex]( {x}^{2} + 3) ^{2} + 7 {x}^{2} + 21 = - 10 \\ [/tex]

[tex]( {x}^{2} + 3) ^{2} + 7 {x}^{2} + 21 = - 10 \\ {m}^{2} + 7 \times m- 3 + 21 = - 10 \\ {m}^{2} +7m + 18= - 10 \\ {m}^{2} + 7m + 18+ 10 = 0 \\ {m}^{2} + 7m + 28 = 0[/tex]

Other Questions